Hubungan Antara Dukungan Teman Sebaya Terhadap Tingkat Kesehatan Mental pada Remaja - Jihan Tri Anggarjita; Betie Febriana; Wahyu Endang Setyowati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Peers have important factors that can influence a person's ability to realize themselves. With peer support, a person has friends who respect, understand, and feel like they have the same friends as themselves. Poor peer relationships can lead to problematic friendships. friendships that experience peer pressure, such as being excluded from groups or friends due to differences of opinion or lack of perspective, will experience setbacks. Peer support greatly influences mental health in adolescents. Knowledge and understanding of mental health, especially in the adolescent phase, is very important to increase adolescents' ability to help themselves in the field of mental health, prepare themselves to face mental health risks, and improve mental health. One way to deal with mental health problems for teenagers is to provide support to increase concern for others. This research is a quantitative research with a cross-sectional approach. Data collection was carried out using a questionnaire on 74 respondents. This research uses a total sampling technique and is processed statistically with the correlation test used in this research is the gamma test. The results of the gamma test on peer support data with the level of mental health in adolescents obtained a p value of 0.022 (<0.05) which shows that Ha is accepted or there is a relationship and the closeness of the relationship is quite strong (-0.745) and the direction of the relationship is negative. There is a relationship between peer support and the level of mental health in adolescents